Establishment of Big Data Index System of Water Resources Scheduling in Pearl River Basin - JIANG Liangyong; LI Jiqing; CHEN Siyu (Renmin Zhujiang)
With the rapid development of society and economy in Pearl River Basin, thecontradiction between water supply and demand is increasingly serious. Therefore, it is urgent toconstruct a set of big data index system for water resources scheduling in Pearl River Basin.Under the guidance of binary water cycle theory, and based on analytic hierarchy process andinformation resource planning method, this paper determines the six goals, i.e. flood control,power generation, water supply, saltwater resistance, shipping and ecological security in PearlRiver Basin, and fuses the measured data such as hydrometeorology, stage-discharge, water qualityand water ecology during water resources scheduling in the Pearl River Basin under the conditionof the Internet of Things and auxiliary information such as humanity and economy, ecologicalenvironment, flood disaster and Internet, classifies all indexes of the pressure term, state termand response term, and establishes the big data index system of water resources scheduling inPearl River Basin based on “Pressure-State-Response (PSR)”model, which provides a decision basisfor water resources management and scheduling in Pearl River Basin.